AMERICAN CULTURAL VALUES REFLECTED IN THE AMERICAN MUSICAL – DRAMA TELEVISION SERIES “GLEE” = Giá trị văn hóa Mỹ phản ánh trong loạt phim truyền hình Mỹ “Glee” - Đinh, Kim Anh (2020)
The agreeableness of film in general and series film in particular in cultural perspective is the main inspiration of this research. This study is aimed at the realization of reflection of American cultural values in the series “Glee” and the implication of the usefulness of films in understanding Cross – Culture Communication To satisfy these research objectives, several instruments, are utilized effectively by the author. This study study employs qualitative method with the two main instruments. Film analysis and observation are likely to be recognized as the most notable instrument which assists the author to reach the majority of research objectives. It is revealed in the study that the series film “Glee” displays clearly nine American cultural values targeted in the literature review, namely, individual freedom, self – reliance, equality of opportunity, competition, material wealth, hard work, directness and openness, informality and practicality. Besides, the author expects to recommend the helpfulness of using movies in the study of Cross – Culture Communication.